a) FeO + H2SO4 = FeSO4 + H2O
FeO + 2H(+) + SO4(2-) = Fe(2+) + SO4(2-) + H2O
FeO + 2H(+) = Fe(2+) + H2O
FeSO4 + 2KOH = Fe(OH)2 + K2SO4
Fe(2+) + SO4(2-) + 2K(+) + 2OH(-) = Fe(OH)2 + 2K(+) + SO4(2-)
Fe(2+) + 2OH(-) = Fe(OH)2
б) ZnO + H2SO4 = ZnSO4 + H2O
ZnO + 2H(+) + SO4(2-) = Zn(2+) + SO4(2-) + H2O
ZnO + 2H(+) = Zn(2+) + H2O
ZnSO4 + 2NaOH = Zn(OH)2 + Na2SO4
Zn(2+) + SO4(2-) + 2Na(+) + 2OH(-) = Zn(OH)2 + 2Na(+) + SO4(2-)
Zn(2+) + 2OH(-) = Zn(OH)2
Zn + H2SO4разб = ZnSO4 + H2
Zn(0) - 2e = Zn(+2) | 1 восстановитель, окисление
2H(+) + 2e = H2(0) | 1 окислитель, восстановление
4Zn + 5H2SO4конц = 4ZnSO4 + H2S + 4H2O
Zn(0) - 2e = Zn(+2) | 8 | 4 восстановитель, окисление
S(+6) + 8e = S(-2) | 2 | 1 окислитель, восстановление
Cu + 2H2SO4конц = CuSO4 + SO2 + 2H2O
Cu(0) - 2e = Cu(+2) | 1 восстановитель, окисление
S(+6) + 2e = S(+4) | 1 окислитель, восстановление